2018
DOI: 10.1002/chem.201802554
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Simulation Verifies the Stability of an 18‐Coordinated Actinium–Helium Complex

Abstract: Structures of a trivalent actinium cation in helium clusters (Ac ⋅He ) have been studied by quantum path integral molecular dynamics simulations with different cluster sizes, n=18-200. The nuclear quantum effect of helium atoms plays an important role in the vibrational amplitude of the Ac -He complex at low temperatures (1-3 K) at which the complex is stable. We found that the coordination number of helium atoms comprising the first solvation shell can be as high as eighteen. In this case, the helium atoms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…The data in the previous section indicate that this difference arises from the omission of BSSE in our previous benchmarking CCSD(T) calculations, which generated an Ac 3+ -He well which was too deep, and hence led to our using the HFS approach. The optimized structure of AcHe 18 3+ is shown in Figure 2(a); it is close to a distorted tetrakis cuboctahedron and has D 4d symmetry, as reported by Ozama et al 16 Efforts to coordinate 19 and 20 He atoms in the primary shell all failed. The stability of AcHe 18 3+ was studied by AIMD at 10 K, starting from the initial geometry shown in Figure 2(a).…”
Section: Ac 3+ -He Complexessupporting
confidence: 54%
See 2 more Smart Citations
“…The data in the previous section indicate that this difference arises from the omission of BSSE in our previous benchmarking CCSD(T) calculations, which generated an Ac 3+ -He well which was too deep, and hence led to our using the HFS approach. The optimized structure of AcHe 18 3+ is shown in Figure 2(a); it is close to a distorted tetrakis cuboctahedron and has D 4d symmetry, as reported by Ozama et al 16 Efforts to coordinate 19 and 20 He atoms in the primary shell all failed. The stability of AcHe 18 3+ was studied by AIMD at 10 K, starting from the initial geometry shown in Figure 2(a).…”
Section: Ac 3+ -He Complexessupporting
confidence: 54%
“…However, a year later, AcHe 18 3+ was reported by Ozama et al, using coupled cluster theory and path integral molecular dynamics (PIMD). 16 According to their work, 18 He atoms can be accommodated in the first coordination shell, in a highly symmetrical D 4d structure, the increase in CN from our work potentially being due to omission of basis set superposition error (BSSE) in our CCSD(T) calculations. Although CN higher than 18 has recently been reported for M(H 2 ) 12 n+ (M = Ac, Th, Pa, U, La, n = 3, 4) 17 and An(BH) 24 (An = Th-Cm), 18 genuine CNs of 24 are debatable given the strong H-H interaction in M(H 2 ) 12 n+ and lack of direct evidence for true 24 M-B bonds in An(BH) 24 .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, the quest for a large CN (i.e., >10) remains underexplored in the realm of metal complexes or coordination polymers, wherein high CNs are originally designed by combining large actinide centers with small ligands. A CN of 15 was experimentally revealed in a thorium aminodiboranate complex, while a CN of 17–24 in actinide complexes with H, He, or BH was suggested based on relativistic quantum chemical calculations. To date, the highest experimentally characterized and theoretically predicted CNs are 16 in the CoB 16 cluster and 28 in a Ta@B 28 3+ complex, respectively.…”
mentioning
confidence: 99%
“…13,[22][23][24][25][26] Other theoretical studies investigated the maximum possible coordination number of Ac 3+ and found that up to 18 helium atoms can be accommodated giving a stable complex [AcHe 18 ] 3+ in the gas phase. 27,28 The current study focuses on the Ac 3+ coordination chemistry and its affinity toward hard/soft bases. A total of 35 ligands was selected (Figure 1 and Table S1, Supporting Information).…”
mentioning
confidence: 99%